"Performing Developability:" Generating threat and value in private land conservation. Issue 128 (January 2022) - Kay, Kelly
Highlights: With an easement, landowners are compensated based on foregone development potential. Real estate appraisers are integral to the valuation process. Landowners can "perform" the threat of conversion to generate greater benefits. Three major strategies are employed: spatial, volumetric, and temporal. Geographers interested in value should engage with property appraisal. Abstract: The majority of private conservation in the United States today is financed by the state and federal tax systems (Kay, 2016), with conservation organizations and private landowners relying in particular on what is one of the "most generous charitable deductions in the federal tax code" (Elkind, 2017). While this has incentivized huge amounts of land protection, it has also increasingly attracted fraudulent activity. In this paper, I look at two cases: the growing market in syndicated conservation easements in Georgia, and the long-troubled program for tradeable conservation easement tax credits in Colorado. These cases are not intended to be comparative, and the choice of such extreme cases is intended to highlight worst-case outcomes of everyday logics and practices. Since conservation easements are required to be valued by a qualified real estate appraiser using an indirect before-and-after valuation approach rooted in notions of highest and best use, landowners must be able to demonstrate development threat in order to be compensated for their easement donation. As a result, those properties under greatest threat of conversion will produce the greatest compensation for their owners. Understanding how this process works allows speculators and developers to be able to mimic the same types of threats that are understood to organically produce valuable conservation easements, generating large financial windfalls. I describe this process as "performing developability, " and drawing on study findings, I highlight three major strategies by which development potential can be performed: spatial, volumetric, and temporal, providing empirical substantiation for each. The paper concludes by questioning the logics of using real estate techniques to value conservation benefits and raises the need for geographers—particularly those interested in market-making—to engage more closely with the practices and logics of property appraisal.